A review on bromhexine hydrochloride and the different analytical methods used for its determination - KELVIN BUCKTOWAR, (International Journal of Pharma and Bio Sciences, 2017)
Bromhexine hydrochloride is a mucolytic agent (expectorant) used in the treatment of respiratory disorders associated with viscid or excessive mucus. The active ingredient Bromhexine hydrochloride is an expectorant which works by loosening mucus in the chest, making it easier to cough up secretions. It is also used to treat productive, chesty coughs. It is chemically named 2-amino-3,5-dibromobenzyl (cyclohexyl) methylamine hydrochloride. According to IUPAC it is 2,4-dibromo-6-[[cyclohexyl (methyl) amino] methyl] aniline; hydrochloride. Bromhexine hydrochloride is a synthetic substance obtained as a synthetic analog of vasicine, a substance found in plants called Adhtoda vasica. The mechanism of action is based on phlegm degradation, thereby easing coughs. The different analytical methods used to quantify the drug as a single active pharmaceutical ingredient includes flow injection analysis with ion selective electrodes, inductively coupled plasma mass spectrometry, electrokinetic chromatography, electrochemical oxidation at the glassy carbon electrode, liquid chromatography, liquid gas chromatography, GC with mass detection, and Voltammetry. The drug has also been quantified in its combined formulations using HPLC, direct and derivative UV spectrophotometry.